2019
DOI: 10.1186/s12871-019-0816-5
|View full text |Cite
|
Sign up to set email alerts
|

Premedication with dexmedetomidine to reduce emergence agitation: a randomized controlled trial

Abstract: Background Nasal bone fracture is the most common type of facial fracture, and the high incidence of severe emergence agitation occurring after closed reduction of the nasal bone fracture can be challenging to manage. The purpose of this trial was to evaluate whether pre-operative administration of dexmedetomidine is effective in reducing the incidence and severity of emergence agitation in adults undergoing closed reduction of nasal bone fractures. Methods In this rand… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 21 publications
0
20
0
Order By: Relevance
“…One of the most common problems in the recovery ward is delayed recovery and longer discharge time of patients receiving pre-operative or intra-operative dexmedetomidine infusion. ( 19 , 21 , 22 ) In our research, the duration of the recovery ward stay was significantly longer in the DA group than in the KA group. However, two groups were similar in terms of total anesthesia time and awakening time.…”
Section: Discussionmentioning
confidence: 43%
See 1 more Smart Citation
“…One of the most common problems in the recovery ward is delayed recovery and longer discharge time of patients receiving pre-operative or intra-operative dexmedetomidine infusion. ( 19 , 21 , 22 ) In our research, the duration of the recovery ward stay was significantly longer in the DA group than in the KA group. However, two groups were similar in terms of total anesthesia time and awakening time.…”
Section: Discussionmentioning
confidence: 43%
“…Kim et al ( 22 ) stated that pre-operative administration of dexmedetomidine in a closed reduction of nasal bone fractures reduces agitation severity and shortens the duration of agitation and also provided more stable maintenance of anesthesia with less movement during the operation.…”
Section: Discussionmentioning
confidence: 99%
“…Lidocaine constant rate infusion (CRI) is associated with sedation [ 31 ]. Clinical trials proved that dexmedetomidine administration decreased the rate of agitation [ 32 , 33 ] and shivering [ 34 ]. In our study, severe bradycardia was not observed during the combined infusion of lidocaine plus dexmedetomidine and dexmedetomidine alone.…”
Section: Discussionmentioning
confidence: 99%
“…Immediate restoration of the top task performance by an α2-adrenergic antagonist in the current study is promising and suggests its future clinical role in active awakening. Although dexmedetomidine per se has been shown to reduce emergence delirium and agitation in humans ( Kim et al, 2019 ; Shi et al, 2019 ), it is possible that other anesthetics could benefit from active awakening and bypassing an intermediate recovery state where delirium and agitation are often observed.…”
Section: Discussionmentioning
confidence: 99%